The determinants of citizens' satisfaction in the water public service: the case study of the governorate of Fayoum - El Rassass, Mona Salem (AUC Knowledge Fountain, 2013)
This empirical study aims at investigating the determinants that influence the level of citizens' satisfaction regarding the water public service. It provides the policy makers and the management of the water companies, with scientific evidence on the factors that control the citizens' satisfaction, and the potential areas of water service improvement. The study used a primary data from a survey of 3000 respondents, collected by the Social Contract Center in December 2011 in the governorate of Fayoum. The investigated variables of this study have been classified into two main groups; the first group is the service-related variables, which included variables related to the water quality, and service quality. The second group is the non service-related variables, which included the socioeconomic, and the demographic variables. For the service-related variables, the study has found that the variables of water quality (i.e. water taste, color, and smell) were all significant in influencing the level of citizens' satisfaction, where the satisfaction varied according to the incidents of facing problems in the water quality. For the variables investigated under the service quality, the study has found that only water pressure, continuity of water flow during the day, and the water company's response to the service urgent needs were significant in influencing the citizens' satisfaction level, while the other variables of having a functioning water meter, facing problems in water bills, and accessibility to the water service information were not influential in affecting the citizens' level of satisfaction regarding the water public service. For the non service-related variables, the study has found that regarding the socioeconomic characteristics of the citizens, the education level of respondents was significant in affecting their level of satisfaction; while on the contrary, the monthly spending average of the household has not show any significance. The demographic characteristics of the citizens have been investigated, and showed that, the gender, and rural-urban distribution of the citizens were significant in affecting the level of satisfaction regarding the water service, yet, the citizens' age failed to show a significant influence. The findings of the study highlight the importance of improving the service-related factors, in order for the water companies to increase the level of citizens' satisfaction with the service.